The Political Hamlet According to Jan Kott and Jerzy Grotowski - Świątkowska, Wanda (Multicultural Shakespeare: Translation, Appropriation and Performance, 2018)
The article presents political interpretations of Hamlet in Poland in the turbulent period of politcal changes between the mid-1950s and mid-1960s. The author discusses the relationships between Shakespeare’s tragedy and Polish political context as well as the influence of audience expectations in the specific interpretations. The selected performances are: Hamlet by Roman Zawistowski (at the Old Theatre in Cracow 1956) and Hamlet Study by Jerzy Grotowski (at the Laboratory Theatre of 13 Rows in Opole 1964). They both were hugely influenced by major commentators of Hamlet, i.e. Stanisław Wyspiański and Jan Kott. The author argues that up-to-date readings of Hamlet, which started with Wyspiański’s study in 1905, flourished in the mid-1950s and mid-1960s when concerning specific political events: the Polish Thaw of 1956 and March 1968, when the Jews were expelled from Poland. Thus Hamlet of that time was updated and must be seen through the prism of political events.